ANALISIS KEGIATAN EKSTRAKURIKULER TILAWAH DALAM PENGEMBANGAN KEMAMPUAN SENI MEMBACA AL QURAN PESERTA DIDIK DI SD UNGGULAN: Analysis Of Extracurricular Activities Of Tilawah ​​In Developing The Art Of Reading The Quran Of Students At Sd Unggulan - Sultansyah, Panji; Nurjannah; Amrullah (STAI Ma'had Aly Al-Hikam Malang, 2024)
Abstract This research is motivated by the fact that there are still many students who have difficulty in reading the Al-Quran, the lack of motivation and support from parents in reading the Al-Quran and the interest of students in participating in extracurricular recitations is still very minimal at the 'Aisyiyah Taman Harapan Curup Primary School. , even though recitations are one of the appropriate methods to overcome problems for students who cannot read the Al-Quran fluently properly and correctly according to the rules of the science of recitation. The aims of this research are: (1) To determine the implementation of extracurricular recitations to improve students' ability to read the Al-Quran at the 'Aisyiyah Taman Harapan Curup Primary School. (2) To determine students' ability to read the Al-Quran after taking part in extracurricular recitations at the 'Aisyiyah Taman Harapan Curup Primary School. This research is a descriptive qualitative case study research. Data collection techniques through observation, interviews and documentation. Then the data analysis technique uses data reduction, data presentation, and conclusions or verification as well as testing the credibility of the data using triangulation of sources and techniques (methods). The results of the research that we want to know are about extracurricular recitation activities in developing students' ability to read the Al-Quran and see the quality of the art of reading the Al-Quran of students who take part in extracurricular recitations at the 'Aisyiyah Taman Harapan Curup Primary School. Penelitian ini di latar belakangi oleh masih banyak peserta didik yang memiliki kesulitan dalam membaca Al Quran, kurangnya motivasi dan dukungan dari orang tua dalam membaca Al Quran serta minat dari peserta didik untuk mengikuti ekstrakurikuler tilawah ini masih sangat minim di SD Unggulan ‘Aisyiyah Taman Harapan Curup, padahal tilawah merupakan salah satu metode yang tepat untuk mengatasi masalah bagi peserta didik yang belum bisa membaca Al Quran dengan lancar secara baik dan benar sesuai kaidah ilmu tajwid. Tujuan dari penelitian ini yaitu : (1) Untuk mengetahui Implementasi Ekstrakurikuler tilawah untuk meningkatkan kemampuan seni membaca Al Quran peserta didik di Sekolah Dasar Unggulan ‘Aisyiyah Taman Harapan Curup. (2) Untuk mengetahui kemampuan seni membaca Al Quran peserta didik setelah mengikuti ekstrakurikuler tilawah di SD Unggulan ‘Aisyiyah Taman Harapan Curup. Penelitian ini merupakan penelitian Studi Kasus yang bersifat deskriptif kualitatif. Teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Kemudian teknik analisis data menggunakan reduksi data, penyajian data, dan kesimpulan atau verifikasi serta uji kredibilitas data menggunakan triangulasi sumber dan teknik (metode). Hasil penelitian yang ingin diketahui ialah tentang kegiatan ekstrakurikuler tilawah dalam pengembangan kemampuan seni membaca Al Quran peserta didik dan melihat kualitas seni membaca Al Quran peserta didik yang mengikuti ekstrakurikuler tilawah di SD Unggulan ‘Aisyiyah Taman Harapan Curup. Kata Kunci : Ekstrakurikuler Tilawah; Seni Membaca Al Quran